Microbial community structure associated to Arctic cold seeps - Carrier, Vincent (UiT The Arctic University of Norway, 2021)
Cold seeps are locations on the seafloor where CH 4 migrates from reservoirs below sediments towards the atmosphere, sustaining thereby a high microbial and macrofaunal biomass and a diversity contrasting from the surrounding seafloor. The oxidation of methane and sulphide are typically the main sources of primary productivity of these ecosystems and have therefore gained a particular attention in the global oceans. Yet, despite the ubiquitous presence of these seeping sites and the presence of gas hydrates in the Arctic Ocean and its adjacent shelves, the impact of methane on benthic and pelagic microbial communities in this region have remained limited. Recently, five gas hydrate bearing mounds with ongoing methane seeping activity were discovered south of Svalbard, in the northern Barents Sea. In this PhD project, I studied changes in the structure of microbial communities, including both prokaryotes and eukaryotes, and geochemical profiles at these mounds to highlight key microbial groups and to provide insights on their ecological roles. Different niches were addressed, including: deep anaerobic sediments (Paper I and II); niches at the sediment surface at gas flare locations and within bacterial mats and siboglinid fields (Paper III); and above gas flares in the shallow shelf water column (Paper IV). The microbial biodiversity and the structure of communities were successfully identified for each of the habitats listed above. Our investigations revealed a microbial composition similar to other cold seeps: a predominance of archaeal anaerobic methanotrophs (ANME) and sulphate-reducing bacteria (SRB) in CH 4 -rich sediments, a higher abundance of methane oxidizing bacteria associated to the Methylococcales in the surface sediments and water column; and a co-occurrence of other commonly found prokaryotic groups. Yet, uncommon biological traits were also uncovered at these methane seeping sites: the anaerobic oxidation of methane was merely only driven by ANME-1 without the co-occurrence of a specific SRB ...